Utility of Fundus Autofluorescence and Optical Coherence Tomography in Measuring Retinal Vascular Thickness, Macular Density, and Ophthalmic Manifestations in Women with Gestational Diabetes Mellitus - Rami Al-Dwairi; Omar Altal; Marwa Fares; Sharaf H. Adi; Shahed A. Said; Asmaa Shurair; Rania Al-Bataineh; Ihsan Aljarrah; Seren Al Beiruti; Ahmed H. Al Sharie; Abdelwahab Aleshawi (Life)
Background: Gestational diabetes mellitus (GDM) is a transient elevation of blood glucose during pregnancy. It is typically not associated with diabetic retinopathy. However, certain investigators revealed retinal microvascular injury. In this study, we aimed to assess the ophthalmic findings, optical coherence tomography (OCT) parameters, and retinal vascular thickness and macular density through fundus autofluorescence (FAF). Methods: Prospectively, women diagnosed with GDM were enrolled in this study. All the participants underwent comprehensive ophthalmic examination. Furthermore, macular OCT with analysis of the central subfield thickness (CST) and total thickness was carried out. Moreover, FAF was performed, and the macular density and retinal vascular thickness were extracted using ImageJ software. Results: Thirty-four women were enrolled. The mean maternal age was 32.7 years. No participant had diabetic retinopathy, nine eyes had early cataract, and two eyes had keratoconus. Higher levels for the 1 h oral glucose tolerance test (OGTT) were associated with a drop in the CST and total thickness. Moreover, women who underwent CS had higher levels of total thickness. Higher levels for the fasting OGTT were associated with a thinner inferior temporal retinal artery. Pregnant women with miscarriages had lower macular density on FAF, as represented by lower values of integrated density and mean gray values. Higher levels for the fasting OGTT were associated with higher values of integrated density. Conclusions: Although GDM is typically not associated with diabetic retinopathy, microscopic changes involving the microvascular environment and the macula may occur. Regular ophthalmic screening for women with GDM may be advised. Larger studies with more investigations may reveal further findings.